Drug reaction with eosinophilia and systemic symptoms (DRESS) in children - Mori, Francesca; Caffarelli, Carlo; Caimmi, Silvia; Bottau, Paolo; Liotti, Lucia; Franceschini, Fabrizio; Cardinale, Fabio; Bernardini, Roberto; Crisafulli, Giuseppe; Saretta, Francesca; Novembre, Elio (Acta Biomedica Atenei Parmensis, 2019)
Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) is a severe reaction to drugs. Incidence of DRESS in children is not well known and the mortality rate seems to be lower than 10%. Anticonvulsants are the main drugs involved both in adults and in children. The treatment of choice is intravenous immunoglobulins and corticosteroids used in synergy. Today there are not controlled clinical trials regarding DRESS treatment in children. Anyway, the prompt withdrawn of the offending drug is of paramount importance for a better prognosis. DRESS sequels may occur, consequently, follow-up visits are required at least until the first year after the reaction.